ANALISIS STUDI KELAYAKAN USAHA PADA UMKM TOKO SINAR - filia helwend; IMELDI SASABONE; DELAVITA RATULOHAIN; MELANY SOUMOKIL; SELVI INGGRIT TUAKORA; MINARSY LESSY (Jurnal Multidisipliner Kapalamada, 2025)
This study aims to analyze the business feasibility of MSME Toko Sinar from the market and marketing aspects. The research adopts a qualitative field research approach, with Toko Sinar MSME as the object of study. Data were collected through in-depth interviews, direct observation, and documentation involving the main informant, the business owner Rian Sinaga. The analysis focuses on market and marketing components, including product, pricing, location, distribution, and promotion. The results indicate that Toko Sinar is feasible from the market and marketing perspectives. The products offered have established brand identity, attractive names, and appealing packaging that enhances consumer interest. Pricing strategies are considered affordable and aligned with the target market’s purchasing power. The business location is strategic and supported by accessible distribution channels, facilitating consumer reach. Furthermore, the promotional strategies implemented are attractive and relatively effective in expanding market coverage. These findings suggest that Toko Sinar has strong potential for sustainable business development and improved market competitiveness.